Creating change in responsible tourism management through social marketing - R. George; N. Frey (South African Journal of Business Management, 2010)
The global threat of climate change, diminishing natural resources and significant socio-economic inequalities is forcing companies and individuals to evaluate the impact they are having on the natural, social and economic environments. This trend has led to an increased availability and demand for socially, environmentally and economically responsible products. The tourism industry relies heavily on the sustained beauty and hospitality of the places and communities it operates in and has come under pressure to manage its negative impacts. Change in the industry has, however, been limited. This paper investigates the current attitudes and perceptions of tourism business owners in Cape Town towards responsible tourism management (RTM) practices in order to develop social marketing strategies that can influence positive behaviour change in management. Cape Town as an internationally acclaimed top tourism destination needs to urgently address its low levels of responsible tourism evidence. Survey data of 244 tourism businesses was used to statistically test what factors are causing the low levels of RTM practices in Cape Town. Findings suggest that despite general positive attitudes towards RTM, tourism businesses are not investing time and money into changing management practices. This is a common emerging market phenomenon where resource constraints negatively impact the relationship between what businesses would like to do and what actually gets done. Factors such as the perceived cost of RTM, a highly competitive environment and a perceived lack of government support are further negatively influencing this relationship. Recommendations are made as to how social marketing can be used to encourage businesses to adopt RTM practices by reducing the perceived and actual costs of implementing RTM. The paper discusses what channels should be implemented to facilitate change.
Keywords: 650